Pelatihan Pembuatan Media Pembelajaran Bahasa Indonesia pada Guru SMK Se Kecamatan Karangpucung - Lutfi Eskawati; Dwi Setiawan; Nita Oktaviani (Universitas Muhammadiyah Manado, 2021)
Learning media has an important role in increasing students’ understanding and retention, attracting their attention, and supporting various learning styles. In the context of Vocational High Schools (SMK), where students tend to be more interested in practical learning, developing relevant and interesting learning media is crucial, especially for Indonesian language subjects. This article discusses the importance of training for vocational school teachers in creating effective learning media. This training aims to increase the understanding of vocational school teachers in Karangpucung sub-district about the concept of learning media, equip them with technical skills in making media, and integrate information and communication technology (ICT) in the learning process. Through stages that include theory, practice and feedback, this training is expected to increase teacher creativity and student learning motivation. Overall, this training contributes to improving the quality of Indonesian language learning in vocational schools, creating a more dynamic and effective learning environment.